Survival Analisis Suhu Tubuh pada Pasien Diare yang Diberikan Vitamin D - Sutrimo Usali R; Endang Darmawan; Nurcholid Umam Kurniawan (Jurnal Surya Medika (JSM), 2020)
Diarrhea is a disease that attacks the digestive system, and most caused by microorganisms (bacteria and viruses) Diarrhea is still the second largest cause of death in the world after pneumonia and is still a public health problem in developing countries like Indonesia. Vitamin D is a potential mediator in regulating the immune system to become the body's defense against infection. This study aims to determine the effectiveness of vitamin D based on body temperature parameters. The study was conducted using a double-blind randomized clinical trial experimental research design, in which researchers conducted clinical trials in the control group (placebo) and there was a comparison group (vitamin D adjuvant). Vitamin D provides a better chance of survival as well as a better chance of a decrease in body temperature compared to patients who do not get vitamin D therapy as an adjuvant (additional). Significant results occurred on days 3, 5 and 6.